2003
DOI: 10.1063/1.1519510
|View full text |Cite
|
Sign up to set email alerts
|

Control and manipulation of solitary structures in a nonlinear optical single feedback experiment

Abstract: We report on the addressing and control of the lateral positions of optical spatial solitary structures in a single feedback experiment with a saturable Kerr nonlinearity. Solitary structures allow a locally self-confined switching between a dark background and a bright state. This binary character can be of use to all-optically route information in optical networks. In general the lateral positions of solitary structures are strongly influenced by mutual interactions and system inhomogeneities. For potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…It was shown that well-defined lock-in distances between the spots can be connected to the formation of oscillatory tails [273,277]. Arrangements of DSs were not only found to be stationary, but propagating [277] and rotating [279]. However, drift was produced by introducing spatial gradients in the system, while rotation was found in the above mentioned systems by choosing D ¼ 2 n þ , with ( 1 in the feedback loop.…”
Section: Advances In Physics 557mentioning
confidence: 92%
See 2 more Smart Citations
“…It was shown that well-defined lock-in distances between the spots can be connected to the formation of oscillatory tails [273,277]. Arrangements of DSs were not only found to be stationary, but propagating [277] and rotating [279]. However, drift was produced by introducing spatial gradients in the system, while rotation was found in the above mentioned systems by choosing D ¼ 2 n þ , with ( 1 in the feedback loop.…”
Section: Advances In Physics 557mentioning
confidence: 92%
“…Different possible lock-in distances for oscillatorily decaying spots were detected for the same parameters, depending on the initial conditions [273,274,277]. Examples for this kind of molecule formation in the system shown in Figure 44 are depicted in Figure 45(d)-(f).…”
Section: Advances In Physics 557mentioning
confidence: 96%
See 1 more Smart Citation
“…In this Report, we describe an all-optical switch that combines the extreme sensitivity of instability-generated transverse optical patterns to tiny perturbations (12)(13)(14)(15)(16) with quantum interference methods (3)(4)(5)(6)(7)(8)(9)(10). A transverse optical pattern is the spatial structure of the electromagnetic field in the plane perpendicular to the propagation direction.…”
mentioning
confidence: 99%
“…It has been shown that cavity solitons can be written and erased throughout the transverse aperture of the device, 27 and spatial-temporal instabilities can be controlled using weak, spatially filtered feedback. 26 In many of the experimental investigations, a semiconductor material 28 (liquid crystal device 29 ) is used as the nonlinear material for which the nonlinear coupling coefficient (response time) was low (slow), thus requiring a large switching energy density in comparison to the atomic experiments described in Sec. 1.1.…”
Section: Switching Using Spontaneously-formed Transverse Optical Pattmentioning
confidence: 99%